The characterisation of paint binders in the polychromies and gildings of the Gandharan artworks - Ilaria Bonaduce; Anna Lluveras Tenorio; Alessia Andreotti; Sibilla Orsini; Maria Perla Colombini; Marialaura Dilillo; Liam Andrew McDonnell (Restauro Archeologico, 2019)
In a polychrome artefact, coloured paint layers are applied on architectural elements or sculptures. Paint layers are made up of the colour, which is most typically an inorganic pigment and, with the exception of frescos, an organic binder, which enables the pigment to be dispersed and applied with a brush. From an analytical point of view the characterisation of organic paint binders is very challenging: the organic matter represents a very small amount of the total weight of the sample which is very small and aged. In this paper we describe the analytical approach applied for the characterisation of samples collected from a selection Gandhara polychromies. The analytical strategies and techniques employed are described and examples of the results obtained are presented.